Bridging Qur’anic Economic Interpretation and Its Relevance to the Contemporary Sharia Financial System - Hanif Afansa Cahya; Ahmad Nurrohim; Muhamad Ali Raaf Sanjani (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to examine in depth the verses of the Qur'an related to the Islamic economic system, especially regarding the prohibition of usury, zakat obligations, the principle of wealth distribution, and the ethics of muamalah, as well as to explore the relevance of the content of these verses to the contemporary Islamic financial system. Theoretical framework: The theoretical framework used departs from the economic principles of the Qur'an, which emphasize justice, transparency, and partiality to the weak, by integrating normative-moral approaches and modern social contexts. Literature review: Previous literature has discussed many Islamic financial products and practices from legal and technical perspectives, but still lacks an explicit link to the comprehensive interpretation of Qur'anic verses. This research bridges this gap by comparing the thought of classical mufassir such as Ibn Kathir and Al-Qurtubi with contemporary mufassir such as M. Quraish Shihab and tafsir at-Tanwir. Method: The method used is qualitative with a thematic interpretation approach (maudhu'i), which involves collecting and analyzing the verses of the Qur'an related to economic themes, then interpreting their meaning, context, and normative message through content analysis of the main interpretation text. Results: The results of the study show that the economic verses in the Qur'an have strong transformative value for forming a fair and inclusive financial system. These values have been partially implemented in the practice of institutions such as Bank Syariah Indonesia, LAZISMU, and Dompet Dhuafa. Implications: The implications of this study confirm that the Islamic financial system should be based not only on fatwas or legal standards, but also on the ethical values of the Qur'an. Novelty: The novelty of this study is an integrative approach between the interpretation of economic verses and the institutional practice of Islamic finance, making it a conceptual and practical foothold in designing a fair and sustainable Islamic economic system.